Metagenomic analysis among water masses and sediments from the Southern Gulf of Mexico - Guerrero, Abraham; Licea, Alexei F.; Lizárraga-Partida, M. L. (Frontiers in Marine Science, 2022)
Selected water masses and sediment samples from the Southern Gulf of Mexico, were studied by bacterial sequencing the 16S rRNA to establish their community structure and discuss the results in relation to those reported by other authors using deep water masses or sediment samples. Forty-five water and 21 sediment samples were collected at selected sampling localities. Proteobacteria was the most abundant phylum of the bacterial community in both environments as well as the class Gammaproteobacteria and the order Alteromonadales. Concerning the family taxonomic category, Alteromonadaceae was the most abundant in the water masses, showing an increase in the deepest water masses. Woeseiaceae and Kiloniellaceae were the most abundant families in the sediments. The statistical pairwise comparison among the water masses showed significant differences between the maximum fluorescence (maxF), the minimum oxygen (minO), the Antarctic Intermediate Water (AAIW), and the North Atlantic Deep Water (NADW) water masses. Also, significant differences were observed between the maxF, minO, AAIW, NADW water masses, and the sediment environment. It was concluded that the maxF water mass showed significant differences in the deepest water masses and that the sediment environment presented a different structure of families from the water environment.